Life cycle analysis for reconstituted decorative lumber from an ecological perspective: A Review - Chengmin Zhou; Ziyan Shi; Jake Kaner (BioResources)
In response to global Sustainable Development Goals (SDGs), the Chinese government has pledged to curtail increased carbon dioxide emissions beyond 2030 and to achieve carbon neutrality by 2060, thus achieving a status of an ecological civilization. Reconstituted decorative lumber, with rotary-cut (or planed) veneer from plantation or common species timber as the main raw material, has beneficial development opportunities for forestry from the perspective of an ecological civilization. This paper first discusses China’s current state of ecological civilization, then researches the various life cycles of reconstituted decorative lumber using the life cycle theory and provides a reference for the Chinese reconstituted decorative lumber industry’s development by analyzing progress in related fields. The eco-friendliness of reconstituted decorative lumber is explained via systematic combing, and proposals for the use and promotion of reconstituted decorative lumber in the new period are presented. Research and analysis findings show that it is necessary to comprehensively regulate the production chain of reconstituted decorative lumber based on life cycle. Research on the development and utilization of reconstituted decorative lumber needs to be strengthened. The promotion and marketing of reconstituted decorative lumber can be promoted by emphasizing its ecological significance.